Likuiditas, Leverage, Profitabilitas, Penilaian Pasar, Firm Size dan Return Saham - Smarabhawa, A. A. Gde Agung; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p020, 2023)
The research aims to obtain empirical evidence of the effect of financial ratios and firm size on stock returns. The research was conducted on consumer goods sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Determination of the sample using nonprobability sampling with purposive sampling. The samples used were 24 companies. The total observation data for the 2018-2020 period is 72 observational data. Methods of data collection using non-participant observation. The analysis technique uses multiple linear regression analysis. Based on the results of the study, it shows that the liquidity ratio has a negative and significant effect, the leverage ratio has a negative and significant effect, the profitability ratio has a negative but not significant effect, the market appraisal ratio has a negative and significant effect, and firm size has a negative but not significant effect on stock returns Keywords : Stock Seturns, Liquidity, Leverage, Profitability, Market Valuation